2012
DOI: 10.1021/bm3007456
|View full text |Cite
|
Sign up to set email alerts
|

State of Degradation in Archeological Oak from the 17th Century Vasa Ship: Substantial Strength Loss Correlates with Reduction in (Holo)Cellulose Molecular Weight

Abstract: In 1628, the Swedish warship Vasa capsized on her maiden voyage and sank in the Stockholm harbor. The ship was recovered in 1961 and, after polyethylene glycol (PEG) impregnation, it was displayed in the Vasa museum. Chemical investigations of the Vasa were undertaken in 2000, and extensive holocellulose degradation was reported at numerous locations in the hull. We have now studied the longitudinal tensile strength of Vasa oak as a function of distance from the surface. The PEG-content, wood density, and cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 20 publications
2
49
0
Order By: Relevance
“…Compared with the reference specimens, the tensile strength of Vasa oak was reduced by an average of 40%, but reductions of up to 80% were also observed [25]. From this summary, it can be concluded that the variation in mechanical properties is large in the oak in the Vasa warship.…”
Section: Mechanical Properties Of Vasa Oak -A Reviewmentioning
confidence: 72%
See 3 more Smart Citations
“…Compared with the reference specimens, the tensile strength of Vasa oak was reduced by an average of 40%, but reductions of up to 80% were also observed [25]. From this summary, it can be concluded that the variation in mechanical properties is large in the oak in the Vasa warship.…”
Section: Mechanical Properties Of Vasa Oak -A Reviewmentioning
confidence: 72%
“…At that time, no differences in mechanical performance were found between samples taken from the interior and the exterior part of the warship [24]. Chemical degradation with a subsequent reduction in strength has been confirmed later on [25]. However, as the majority of the chemical degradation is also believed to have taken place after the salvage [31], Thunell's results [24] are reasonable.…”
Section: Mechanical Properties Of Vasa Oak -A Reviewmentioning
confidence: 98%
See 2 more Smart Citations
“…This procedure aimed at replacing the water in the wood cell walls by PEG and thus preventing shrinkage and formation of cracks during drying (Håfors 2001). Since salt precipitation on numerous surfaces on the ship had been reported (Sandström et al 2002), a series of investigations of the chemistry (Glastrup et al 2006;Almkvist and Persson 2008a, b;Lindfors et al 2008;Almkvist et al 2016) and also of the mechanical properties of Vasa oak wood (Ljungdahl 2006;Bjurhager et al 2012;Vorobyev et al 2016) have been performed over the last years. These research activities showed that the oak wood is affected by degradation, i.e., by depolymerization of polysaccharides.…”
Section: Introductionmentioning
confidence: 99%